Pain in the Ehlers–Danlos syndromes: Mechanisms, models, and challenges. Issue 4 (19th November 2021) - Malfait, Fransiska; Colman, Marlies; Vroman, Robin; De Wandele, Inge; Rombaut, Lies; Miller, Rachel E.; Malfait, Anne‐Marie; Syx, Delfien
Abstract: Chronic pain is one of the most common, yet poorly studied, complaints in people suffering from Ehlers–Danlos syndromes (EDS). This heterogeneous group of heritable connective tissue disorders is typically characterized by skin hyperextensibility, joint hypermobility, and generalized connective tissue fragility. Most EDS types are caused by genetic defects that affect connective tissue biosynthesis, thereby compromising collagen biosynthesis or fibrillogenesis and resulting in a disorganized extracellular matrix. Even though chronic pain is a major source of disability, functional impairment, and psychosocial suffering in EDS, currently used analgesics and other treatment strategies provide inadequate pain relief and thus represents an important unmet medical need. An important contributor to this is the lack of knowledge about the underlying mechanisms. In this narrative review, we summarize the current understanding of pain and the associated mechanisms in EDS based on clinical studies focusing on questionnaires and experimental pain testing as well as studies in animal models of EDS. In addition, we highlight the challenges, gaps, and opportunities in EDS‐pain research.